Forms, importance and working of social institutions - Martti Vihanto (Aboa Centre for Economics (ACE), 2009)
Social institutions are persistent regularities in contracting and other relations amongst men and in the unintended consequences of such rule-like behavior. They include morality and law as well as institutions of governance such as branding and advertising. Institutions are studied in all approaches and schools of economics, and each involves its peculiar emphases. The purpose of the paper is to give an overview of the forms, importance and working of social institutions by taking examples from decision making of consumers. Use is made in particular of the findings of transaction-cost, evolutionary and behavioral economics. The paper is part of a Finnish open access textbook Principles of Institutional Economics in progress (www.ace-economics.fi/mvihanto).
Keywords: B52; D11; D02; 330; social institutions; institutional economics; transaction costs; heuristic behavior